Assessment of farmers’ vulnerability to climate variability and extreme events: Evidence from dry Kitui, Kenya - C.K., Ndung’u; W., Kamau Mercy; F.W, Muriu-Ng’ang’a (International Journal of Environment, Agriculture and Biotechnology, 2021)
Climate variability and extreme events are some of the most pressing environmental challenges occurring in the contemporary world. Farming communities in Sub-Saharan Africa, particularly in arid and semi-arid areas are more vulnerable to climate vulnerability and extremesdue to high dependence on rain-fed agriculture. There is little understanding of factors influencing farmers’ vulnerability to climate variability and extremes at household level in arid and semi-arid parts of Kenya. This study analyzed farmers’ vulnerability to climate variability and extremes in arid and semi-arid parts of Kitui County, Kenya. The study utilized data collected from 341 households from Yuku, Kaveta, Kauwi and Kasaini sub-locations located in four different agro-ecological zones. Descriptive survey was used and purposive sampling method applied in identifying the sub-locations of study. Proportionate sampling was used to select the number of households to be interviewed in each sub-location and systematic sampling used to select the households which formed the units of analysis. Vulnerability analysis was based on indices constructed from carefully selected indicators for exposure, sensitivity, and adaptive capacity. The indicators were weighted using Equal Weight Analysis. Vulnerability indices indicated that Yuku sub-location (arid) was the most vulnerable to climate variability and extreme events (1.487) followed by transitional zone from semi-arid to semi-humid- Kauwi (0.214), semi-arid- Kasaini (0.085) and semi-humid- Kaveta sub-location (-0.530). Development and policy measures should be focused towards improving the adaptive capacity of the rural farming households, while keeping the post-disaster emergency relief measures in place for zones with higher biophysical vulnerability to climate variability and extremes.